STRATEGI GURU DALAM KOMPETENSI LINTAS BUDAYA ANAK IMIGRAN DI AT-TANZIL KOTA DAMANSARA MALAYSIA - Nuriyanto, Ahmad Hinanda; Nurlaili Dina Hafni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Global mobility in the twenty-first century has led to an increasing movement of populations across national borders, including the migration of Indonesian families to multiethnic urban areas such as Kota Damansara, Malaysia. This condition has significant implications for the educational sector, particularly for immigrant children who face challenges related to cultural adaptation, language barriers, and limited access to formal education. This study aims to analyze teachers’ strategies in developing the intercultural competence of Indonesian immigrant children at the At-Tanzil Learning Center in Kota Damansara, identify the challenges encountered in the learning process, and examine the efforts undertaken by teachers to address these obstacles. This research employed a qualitative descriptive approach using field research. The research subjects consisted of Indonesian immigrant children participating in nonformal education at the At-Tanzil Learning Center, teachers, and international community service (KKN) students. Data were collected through participatory observation, in-depth interviews, and documentation. Data analysis was conducted using the interactive model proposed by Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The findings indicate that learning activities at At-Tanzil take place within a multicultural and transnational context by simultaneously integrating Indonesian national values, Nusantara cultural heritage, and Islamic education. Teachers implement experiential thematic learning, collaborative learning models, language integration, and religio-cultural approaches to develop students’ intercultural competence. The main challenges identified include limited resources and cultural curriculum materials, language barriers, restricted instructional time, the psychosocial conditions of immigrant students, and the lack of formal training in multicultural education for teachers. To address these challenges, teachers adapt instructional materials through translanguaging practices, promote peer support, collaborate with parents and the community, engage in internal professional reflection, and apply inclusive psychosocial approaches. This study underscores the strategic role of community-based nonformal education in strengthening intercultural competence and national identity among Indonesian immigrant children living abroad.